Systematic Review on the Impact of Conditional Cash Transfers on Child Health Service Utilisation and Child Health in Sub-Saharan Africa - Onwuchekwa, Chukwuemeka; Verdonck, Kristien; Marchal, Bruno (Frontiers in Public Health, 2021)
Background: Conditional cash transfers (CCTs) are interventions which provide assistance in the form of cash to specific vulnerable groups on the condition that they meet pre-defined requirements. The impact of conditional cash transfers on children’s access to health services and on their overall health has not been established in sub-Saharan Africa. Method: We conducted a systematic review aimed at summarising the available information on the impact of conditional cash transfers on health service utilisation and child health in sub-Saharan Africa. We searched databases for peer-reviewed articles, websites of organisations involved in implementing conditional cash transfer programmes, and Google scholar to identify grey literature. Records were selected based on predefined eligibility criteria which were drawn from a programme impact framework. Records were eligible if one of the following outcomes was evaluated: health services utilisation, immunisation coverage, growth monitoring, anthropometry, illness reported, and mortality. Other records which reported on important intermediate outcomes or described mechanisms significantly contributing to impact were also included in the review. Data items were extracted from eligible records into an extraction form based on predefined data items. Study quality indicators were also extracted into a quality assessment form. Results: Thematic narrative synthesis was conducted using data from nine included records. The review included five cluster randomised evaluations, one quasi-experimental clustered study, one randomised trial at the individual level, one mixed-method study and one purely qualitative study. There was insufficient evidence of an impact of conditional cash transfers on health service utilisation. There was also not enough evidence of an impact on nutritional status. No impact was observed on health status based on illness reports, nor on immunisation rates. None of the included records evaluated the impact on childhood mortality. Conclusions: The findings of this review suggest that a positive impact may be observed in health service utilisation and nutrition, however, this may not translate into improved child health. Further research is needed to understand the mechanisms and pathways by which these interventions work, explore the effect of contextual factors on their impact, and assess their cost implication especially within resource-constrained settings.